Reciclagem química conduzida pelo uso de líquidos iônicos, como estratégia para mitigar a poluição por microplásticos - Neves, Valquiria Lilith Braga das (2024)
Given the challenging issue of microplastic pollution, the study of new processes for removal and recycling of these particles becomes increasingly important. Current technologies face challenges such as high costs and low efficiency. Regarding chemical recycling techniques, there is usually a need for the use of harmful solvents, along with long reaction times, high temperatures, and pressures. Ionic liquids (ILs) emerge as an alternative to these challenges and are increasingly being used in plastic waste recycling processes due to their thermal stability and possibility of reuse, optimizing reaction conditions. This study aimed to chemically recycle polyethylene terephthalate (PET) microplastics using low-toxicity ionic liquids as solvents under mild reaction conditions. The efficiency of converting PET into its main monomer, terephthalic acid, was compared in depolymerization processes involving four distinct protic ionic liquids, named PIL1, PIL2, PIL3, and PIL4. These ILs were synthesized through equimolar reactions between basic compounds like choline hydroxide and formic or acetic acid. They were characterized by physicochemical property analyses. The synthesis of ILs was confirmed through FT-IR and 1H NMR analyses. Cytotoxicity tests against the microcrustacean Artemia salina classified these compounds as low or non-toxic (CL50 > 250 μg/mL). Subsequently, it was demonstrated that all studied ILs could depolymerize PET under mild conditions. However, the ionic liquid [DBNH][OAc] (PIL3) proved to be the most efficient, achieving 99.67% PET conversion and 92.52% TPA yield at 110º C for 30 minutes. Thermogravimetric (TG), microscopy (SEM), NMR, and FTIR analyses confirmed the production of a recycled product similar to commercial terephthalic acid (TPA), enabling its reintroduction into the industry through a more sustainable and cost-effective recycling process.